Genome-wide H3K9 acetylation level increases with age-dependent senescence of flag leaf in rice. (16th April 2022) - Zhang, Yu; Li, Yanyun; Zhang, Yuanyuan; Zhang, Zeyu; Zhang, Deyu; Wang, Xiaonan; Lai, Binfan; Huang, Dandan; Gu, Lianfeng; Xie, Yakun; Miao, Ying
Abstract: Flag leaf senescence is an important biological process that drives the remobilization of nutrients to the growing organs of rice. Leaf senescence is controlled by genetic information via gene expression and histone modification, but the precise mechanism is as yet unclear. Here, we analysed genome-wide acetylated lysine residue 9 of histone H3 (H3K9ac) enrichment by chromatin immunoprecipitation-sequencing (ChIP-seq), and examined its association with transcriptomes by RNA-seq during flag leaf aging in rice ( Oryza sativa ). We found that genome-wide H3K9 acetylation levels increased with age-dependent senescence in rice flag leaf, and there was a positive correlation between the density and breadth of H3K9ac with gene expression and transcript elongation. During flag leaf aging, we observed 1249 up-regulated differentially expressed genes (DEGs) and 996 down-regulated DEGs, showing a strong relationship between temporal changes in gene expression and gain/loss of H3K9ac. We produced a landscape of H3K9 acetylation-modified gene expression targets that include known senescence-associated genes, metabolism-related genes, as well as miRNA biosynthesis-related genes. Our findings reveal a complex regulatory network of metabolism- and senescence-related pathways mediated by H3K9ac, and elucidate patterns of H3K9ac-mediated regulation of gene expression during flag leaf aging in rice. Abstract : Genome-wide H3K9 acetylation level increases with age-dependent senescence in rice flag leaf, and the density and breadth of H3K9ac positively correlate with transcript elongation and expression of many genes involved in a complex metabolism-mediated senescence network.